UPAYA PENINGKATAN PENDAPATAN MASYARAKAT MELALUI PENGOLAHAN MINYAK KELAPA DI KELURAHAN RAHAMPUU KECAMATAN KABAENA KABUPATEN BOMBANA - Nurfidha Jamil; Rosmawaty; Suriana (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
This research is motivated by coconut commodities that thrive in all areas of Indonesia. If processed properly and given serious attention by the government, through coconut derivative products, one of which is coconut oil. Coconut commodities can contribute significantly to increasing the economic income of the community, region, and even country. This study aims to determine the amount of income and marketing strategies carried out to increase the income of coconut oil processors in Rahampuu Village, Kabaena District, Bombana Regency. The population in this study amounted to 20 coconut oil processors. The sample was determined using the census method, so the research sample amounted to 20 respondents. Data collection was conducted using observation, interview, and documentation techniques with the help of research instruments in the form of questionnaires. This research uses a quantitative approach. Data were analyzed using quantitative descriptive methods through identification and description activities and income analysis to determine the amount of income of coconut oil processing communities. The results showed that the income of the coconut oil processing community which was divided into three groups, namely the Eemolo group produced Rp 7,654,506, the Petolea group produced Rp 9,254,365, and the Tangkenokinolo group produced Rp 7,654,143. This group income will then be divided among each group member according to the number of group members. Marketing to increase the income of coconut oil processors in Rahampuu Village, Kabaena Subdistrict, Bombana Regency, is done by using the services of middlemen/collectors. This saves the community the cost of transporting the product from the production site to the Sikeli central market.